Increasing engagement of Hispanics/Latinos in clinical trials on Alzheimer's disease and related dementias. Issue 1 (26th July 2022) - Marquez, David X.; Perez, Adriana; Johnson, Julene K.; Jaldin, Michelle; Pinto, Juan; Keiser, Sahru; Tran, Thi; Martinez, Paula; Guerrero, Javier; Portacolone, Elena
Abstract: Introduction: Despite evidence that Hispanic/Latino populations are 1.5 times more likely than non‐Latino Whites to develop Alzheimer's disease and related dementias (ADRD), Latinos are underrepresented in clinical trials testing treatments for ADRD. Data are needed on facilitators of ADRD clinical trial participation in Latinos. We leveraged in‐depth qualitative methods to elucidate barriers and facilitators to participating in ADRD clinical trials in a large and diverse sample of Latinos; and to provide timely and actionable strategies to accelerate representation of Latinos in clinical trials on ADRD. Methods: Data were collected in California between January 2019 and June 2020 from 25 focus groups (FGs): eight with Latino adults ages 18 to 49 ( n  = 54), nine with Latino adults ages 50+ ( n  = 75), and eight with caregivers of Latino older adults with ADRD ( n  = 52). Twelve community‐based organization administrators were also interviewed. Transcripts of FGs and interviews were entered into Atlas.ti software. Three independent team members analyzed the transcripts with inductive/deductive qualitative content analysis. We triangulated data from stakeholder groups across sites, we used collaborative coding, and used the Consolidated Criteria for Reporting Qualitative Research. Results: An overarching theme was a tension between wanting to learn more about ADRD and to participate in ADRD research but having limited awareness and opportunity. Five themes were identified: (1) remaining in limbo, (2) wanting information about ADRD, (3) wanting information on research about ADRD, (4) clearing researchers through trusted local organizations, and (5) practicing altruism through engagement in research opportunities. Discussion: To increase representation of Latino communities in clinical trials on ADRD, bilingual information and education on ADRD and clinical trials needs to be better disseminated. Also, working with trusted local, regional, and national organizations can increase participation. Importantly, Latino participation can increase when research teams demonstrate altruistic actions and inform participants of public health reasons requiring their involvement. HIGHLIGHTS: Participation in clinical trials on Alzheimer's disease and related dementias (ADRD) is limited among Latinos/Hispanics. Knowing the high prevalence of ADRD in Latinos increases willingness to participate. Observing altruism from researchers increases willingness to participate. Invitations from multiple organizations increases willingness to participate. Researchers should include public health reasons requiring Latinos' involvement.